The Essence of the Customs Security and Its Place in the National Security System of the State - 10.32983/2222-4459-2020-11-76-82 (Bìznes Inform, 2020)
The article is aimed at determining the essence of the category of «customs security» and its place in the national security system of the State. The category of «customs security» and its main components are analyzed. Approaches to interpretation of this category are considered in line with the national legislation and in accordance with the views of leading domestic and foreign scholars. The wording on which it is advisable to rely in further research is defined. The adjacent category of «customs interests of the State» is considered in the context of the analysis of the category of «customs security», the main types of customs interests of Ukraine at the present stage are defined and grouped, also their graphical presentation is provided. It is determined that the scope of all customs interests of the State lies in the plane of achieving certain economic results and compliance with customs legislation by subjects of foreign economic activity and regulatory authorities. An important step of the State in this direction will be to consolidate the list of customs interests at the legislative level, because it still remains undocumented in Ukrainian legislative acts. The role and place of customs security of Ukraine in the national security system of the State are analyzed, which determines that customs security belongs to such part of national security as economic security. Although in the domestic practice of computing the level of economic security the customs security is not singled out as a separate part of economic security, the fact of communication of economic security with customs is indisputable, since the customs interests of the State, the status of protection of which forms customs security, lie in the economic plane. It is found out that customs security is associated with almost all components of economic security, but the closer link is observed between customs and financial security, as well as between customs and foreign security.